A Comprehensive Kinetic Model of Free‐Radical‐Mediated Interfacial Polymerization. Issue 2 (24th January 2013) - Shenoy, Raveesh; Bowman, Christopher N.
Abstract A mathematical model describing interfacial radical polymerization‐based film formation on hydrogels is elucidated. A glucose oxidase‐mediated multistage initiation reaction is used to accomplish interfacial film formation. A polymer concentration‐dependent diffusion coefficient is used to reflect the changing mass transport conditions as the film develops. Model predictions of the film thickness as a function of the species concentrations agree well with experiments. The model predicts that the degree of initiation reaction delocalization with the enzyme‐mediated initiation system is significantly higher than an enzyme‐independent system, thus affecting the film growth rate and structure. The mass transport properties of the film and its adhesion to the underlying substrate are also investigated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>